Vertical Farming and Urban Horticulture in India: Opportunities, Challenges, and Future Prospects - Shadab Ali; Anuradha Singh; Amar Singh Kashyap (International Journal of Trends in Horticulture, 2024)
The management of resources, environmental sustainability, and food security are all seriously threatened by India's fast urbanization. Vertical farming and urban horticulture have emerged as innovative solutions to these challenges, offering the potential to produce fresh food within urban settings while minimizing the environmental footprint. This review article provides a comprehensive analysis of the current state of vertical farming and urban horticulture in India, examining the opportunities, challenges, and future prospects of these practices. The article explores various types of vertical farming and urban horticulture, including rooftop gardens, indoor farms, and community gardens, and highlights successful case studies across Indian cities. It also discusses the economic, environmental, and social benefits of these practices, such as reduced food miles, enhanced urban green spaces, and improved food security. The implementation of vertical farming in India is confronted with various obstacles, such as substantial upfront expenses, energy demands, legal impediments, and the required for specialized expertise.The review concludes by suggesting strategies for overcoming these challenges, such as supportive government policies, public-private partnerships, and research into more energy-efficient technologies. In India, vertical farming and urban horticulture appear to have a bright future ahead of them.to contribute to sustainable urban development and food security.
Keywords: Environmental impact; Food security; India; Sustainable agriculture; Vertical farming; urban horticulture; urbanization